Philippine book of days a calendar of holidays, anniversaries, and festivals - Santos, Minerva E.; Vallejo, Rosa M.; Hidalgo, Namnama P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1980)
The Philippine Book of Days is a list, in calendar order, of religious days, patriotic and civic holidays including historical aniiversaries and important events in the Philippines, birth and death anniversaries of notable Filipinos, special observances, and fiestas and festivals in the Philippines. The calendar listing includes a brief discussion about the historical background, and a description of the customs and celebrations, of each observance.
The work was prepared through the examination of numerous and various printed sources, including books, magazine articles, newspapers, travel guidebooks, and religious and other calendars, and the subsequent recording and compilation of data about names, days, andd events.
The work, which purports to serve as a day-to-day reminder of important people, memorable events, and holidays that have enriched each day in the history of the country, also includes a historical background of the calendar in general and in the Philippines, and notes on holidays and fiestas and their role and significance in Philippine sources, in the bibliography of Philippine holidays and festival terms, and a general index conclude the work.
Typescript
Vita.
Special Problem (Master of Library Science)
Keywords: Anniversaries -- Bibliography; Calendar; Festivals -- Bibliography. -- Philippines; Holidays -- Bibliography. -- Philippines